Reformasi Pemahaman Teori Maqasid Syariah (Analisis Pendekatan Sistem Jasser Audah) - Fasa, Muhammad Iqbal (State Institute of Islamic Studies (IAIN) Palu, 2016)
This paper attempts to offer reform ideas Jasser Auda thought related reforms theoretical understanding of maqá¾±á¹£id sharia. The systems approach is done by Auda critize the theory of classical maqá¾±á¹£id more likely to hierarchical and narrow mindset. The classical maqá¾±á¹£id pressure a point more on protection and preservation. Whereas the new maqá¾±á¹£id theory emphasizes development (construction, development) and rights (rights). Thus, Auda developed the concept of human development as the main target of maslahah (public interest). Auda offers the systems approach, namely: cognitive nature; interrelated; wholeness; openness; multi dimentionality and purposefulness. At the end of the discussion in this paper, the authors develop the idea of Jasser Auda by offering Sharia Maqá¾±á¹£id concept in the context of Islamic Economics